Student overload at university: Large class teaching challenges - Moodley, Samantha (South African Journal of Higher Education, 2016)
Burgeoning class sizes coupled with the traditional didactic means has become a way of navigating around the challenges lecturers face at university. Many issues continue to plague lecturers and students alike which inadvertently impacts on the teaching and learning experience. This study examines the challenges faced by lecturers with large classes at higher education institutions. A study conducted at two universities through the use of questionnaires found that lecturers at both institutions were faced with similar challenges in teaching/lecturing large classes. The current feasible solution to support the traditional form of lecturing is the use of ICT’s in reaching all students within large classes.